2007
DOI: 10.1016/j.jcp.2007.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Model reduction techniques for frequency averaging in radiative heat transfer

Abstract: We study model reduction techniques for frequency averaging in radiative heat transfer. Especially, we employ proper orthogonal decomposition in combination with the method of snapshots to devise an automated a posteriori algorithm, which helps to reduce significantly the dimensionality for further simulations. The reliability of the surrogate models is tested and we compare the results with two other reduced models, which are given by the approximation using the weighted sum of gray gases and by an frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Using equation (18) in equation (16), the approximation of the unassembled nonlinear load f u is given by…”
Section: Udeim Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using equation (18) in equation (16), the approximation of the unassembled nonlinear load f u is given by…”
Section: Udeim Methodsmentioning
confidence: 99%
“…On this basis, Falkiewicz and Cesnik 17 demonstrated that a POD basis identified a priori remains available for the solution of linear heat transfer problem with the change of boundary conditions. Pinnau and Schulze 18 adopted POD to construct a reduced-order model in combination with the well-known SPn model for frequency averaging in radiative heat transfer. Big errors appeared at the boundary of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Second, these data are used to determine the laser input amplitude following the procedure described in Section 4.2. The amplitude of the excitation is assumed not known, and it is approximated following a piecewise linear approximation with n fit D 50 (i.e., a uniform mesh of 51 nodes each 20 ms), see (27). Figure 14 shows the synthetically generated temperature at the monitoring point (left) and a comparison (right) between the approximated nodal values (blue markers) and the reference amplitude (solid red line).…”
Section: Amplitude Identificationmentioning
confidence: 99%
“…Finally, it is important to note that in spite of the large amount of scientific contributions using a frequency domain description in solid dynamics, this approach is not standard, to the author's knowledge, for thermal models subjected to dynamical forced thermal loads. Certainly, time domain approximations of thermal models are both efficient and robust, and moreover, model order reduction is successfully applied in this setting [19][20][21][22][23][24][25][26], whereas frequency domain approaches for thermal studies are scarce [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of radiative transfer, such model reduction techniques have been applied by Pinnau and Schultze [16] for treating the spectral dependence of the radiative intensity. They used a POD method to model the radiative properties of glass and compared their approach to the Weighted-Sum-of-Grey-Gas (WSGG) method and a simple frequency averaging.…”
mentioning
confidence: 99%